In Situ Grown Vertically Oriented Wrinkled MoSe2 Nanosheets over Different Substrates as Bifunctional Electrocatalysts for Water Splitting - Maurya P.K.; Mishra A.K. (My University, 2025)
Hydrogen gas is considered as a valuable fuel source because of its high energy density, clean burning ability, and renewable nature. It can be used to power vehicles, heat homes, and produce electricity. Herein, we report the successful in situ hydrothermal synthesis of vertically oriented wrinkled MoSe2 nanoarchitecture on the surface of Ni foam (MoSe2-Ni foam) and conducting carbon paper (MoSe2-CCP) as binder-free electrodes. The prepared electrodes are characterized using different microscopic and spectroscopic techniques. These electrodes are tested for their electrocatalytic activity in 1 M KOH for the oxygen evolution reaction (OER), while their hydrogen evolution reaction (HER) activity is examined in both basic (1 M KOH) and acidic (0.5 M H2SO4) electrolytes. The OER performance shows lower overpotential (η50) of 292 mV and corresponding Tafel slope of 20 mV dec-1 for the MoSe2-Ni electrode compared to the MoSe2-CCP electrode (η50 ∼ 352 mV, η10 ∼ 296 mV and Tafel slope ∼ 36 mV dec-1) in 1 M KOH at a potential sweep rate of 2 mV s-1. The HER performance in 1 M KOH again reveals that MoSe2-Ni shows better activity (η10 ∼ 101 mV and Tafel slope ∼73 mV dec-1) compared to MoSe2-CCP (η10 ∼ 220 mV and Tafel slope ∼83 mV dec-1). The HER performance in acidic medium shows that the MoSe2-CCP electrode has better activity (η10 ∼ 142 mV and Tafel slope ∼53 mV dec-1) compared to MoSe2-Ni (η10 ∼ 202 mV and Tafel slope ∼144 mV dec-1). Further, we have designed indigenous electrolyzers using these binder-free vertically oriented MoSe2-based electrodes for overall water splitting in a basic medium. These pristine vertically oriented MoSe2 nanoarchitecture-based binder-free electrodes show better performance than pristine MoSe2 reported by other due to the presence of a higher number of active sites in a large number of exposed edges for wrinkled-like structures. © 2023 American Chemical Society